Outreach 2.0: Promoting Archives and Special Collections through Social Media. - Mason, MarissaK. (Public Services Quarterly)
The Future Voices in Public Services column is a forum for students in graduate library and information science programs to discuss key issues they see in academic library public services, to envision what they feel librarians in public service have to offer to academia, to tell us of their visions for the profession, or to tell us of research that is going on in library schools. We hope to provide fresh perspectives from those entering our field, in both the United States and other countries. Interested faculty of graduate library and information science programs, who would like their students' ideas represented in these pages, are invited to contact Nancy H. Dewald at nxd7@psu.edu. Marissa K. Mason is an MSIS student specializing in archives and records management at the University at Albany's Department of Information Studies. In this essay, she discusses the opportunities and challenges of using various social media for promotional outreach of archives and special collections. The University at Albany's Department of Information Studies, part of the College of Computing and Information, offers a broad-based Master of Science in Information Science degree accredited by the American Library Association. The program has concentrations in library and information services, archives and records administration, school library media, information management and policy, and information systems and technology. Students learn how information is created, organized, represented, stored, accessed, retrieved, managed and used. In addition, they investigate the uses and impacts of information and technology on individuals, organizations and society, including formal and informal communities, libraries, government, and business. A required internship course helps ensure that the program's graduates are ready to enter the world of information professionals. For more information, seehttp://www.albany.edu/informationstudies/index.php *****